Combined PSO-FDFD Optimization of Rectangular Ridged Waveguides - Simone, Marco; Fanti, Alessandro; Montisci, Giorgio; Casula, Giovanni Andrea; Mazzarella, Giuseppe (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Finite-difference frequency-domain technique in conjunction with the particle swarm optimization algorithm is presented as an effective procedure for ridged waveguides design optimization. A suitable objective function is furthermore able to deal with the conflicting requirements of wide bandwidth and high power handling capability. Different configurations have been analyzed, and the influence of the algorithm parameters on the optimized structure has been investigated.